PENGARUH CURRENT RATIO DAN LABA BERSIH TERHADAP RETURN SAHAM PERUSAHAAN PULP DAN KERTAS YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Maryana, Ferra; Erwansyah, Ferli (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract, This study aims to give empirical evidence about the effect of current ratio and nett earnings to stock return of pulp and paper sub sector which listed in Indonesia Stock Exchange on 2018-2022. The research population was 8 pulp and paper sub-sector companies. The research sample was 6 companies. Hypothesis testing used multiple linear regression analysis Research result prove that both of current ratio and nett profits have no effect on stock return of pulp and paper sub sector.